The Role of Antibodies in the Pathogenesis of Multiple Sclerosis - Yu, Xiaoli; Graner, Michael; Kennedy, Peter G. E.; Liu, Yiting (Frontiers in Neurology, 2020)
The presence of persistent intrathecal oligoclonal immunoglobulin G (IgG) bands (OCBs) and lesional IgG deposition are seminal features of multiple sclerosis (MS) disease pathology. Despite extensive investigations, the role of antibodies, the products of mature CD19+ B cells, in disease development is still controversial and under significant debate. Recent success of B cell depletion therapies has revealed that CD20+ B cells contribute to MS pathogenesis via both antigen-presentation and T-cell-regulation. However, the limited efficacy of CD20+ B cell depletion therapies for the treatment of progressive MS indicates that additional mechanisms are involved. In this review, we present findings suggesting a potential pathological role for increased intrathecal IgGs, the relation of circulating antibodies to intrathecal IgGs, and the selective elevation of IgG1 and IgG3 subclasses in MS. We propose a working hypothesis that circulating B cells and antibodies contribute significantly to intrathecal IgGs, thereby exerting primary and pathogenic effects in MS development. Increased levels of IgG1 and IgG3 antibodies induce potent antibody-mediated cytotoxicity to central nervous system (CNS) cells and/or reduce the threshold required for antigen-driven antibody clustering leading to optimal activation of immune responses. Direct proof of the pathogenic roles of antibodies in MS may provide opportunities for novel blood biomarker identification as well as strategies for the development of effective therapeutic interventions.